A review of the genus Mirocastnia J. Y. Miller, 1980 (Lepidoptera: Castniidae) with records of recently collected specimens - González, Jorge M.; Thöny, Hubert; Worthy, Robert (Zootaxa, 2024)
A new record of the rare species Mirocastnia pyrrhopygoides (Houlbert) from Ecuador is reported, along with range extensions for M. smalli (J. Y. Miller) and M. canis (Lathy). In addition, the genus Mirocastnia J. Y. Miller is revised and the diagnostic phenotypic characteristics of males and females, as well as male genitalia, are illustrated. Details on its natural history, biogeography, and biology are included with the purpose of solving the confusion in the taxonomy of the genus. All taxa previously considered to be species are herein relegated to subspecific status, i.e. M. pyrrhopygoides canis stat. nov. and M. p. smalli stat. nov.